2015
DOI: 10.3109/10717544.2015.1028603
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue distribution study in mice of triptolide-loaded lipid emulsion and accumulation effect on pancreas

Abstract: Triptolide (TP) shows strong anti-tumor activities on various cancer cells, especially on pancreatic cancer. TP inhibits HSP70 expression leading to cell death in pancreatic cancer cells and induces cell death by apoptotic and autophagic pathways. In order to increase the therapeutic index of TP, a novel intravenous TP-loaded delivery system, TP-loaded lipid emulsion (TP-LE), has been developed to treat solid tumor. In the present study, the preparation and characterization of TP-LE were described. The pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The data were analyzed according to the previous papers (Li et al, 2016 ; Rezazadeh et al, 2016 ). For each group, the concentration-time curve was profiled according to the mean concentration of 6 mice for a point.…”
Section: Methodsmentioning
confidence: 99%
“…The data were analyzed according to the previous papers (Li et al, 2016 ; Rezazadeh et al, 2016 ). For each group, the concentration-time curve was profiled according to the mean concentration of 6 mice for a point.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, TP has attracted immense attention to its anticancer activity with multiple mechanisms, which can reduce drug resistance for cancers [8][9][10][11]. Several studies have shown that TP is more effective against pancreatic cancer compared with gemcitabine, paclitaxel, cisplatin and doxorubicin [12][13][14]. However, its clinical development has been greatly hampered by its poor water solubility (0.017 mg/mL) [15], multi-organ toxicity [16][17][18] and low bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…RA affects about 1% of the population, and it is associated with a large number of medical resources (Feldmann, 2002 ; Malahias et al, 2012 ; Yang et al, 2017 ). Triptolide, a diterpene epoxide, exhibits diverse pharmacological activities, including antirheumatic, analgesic, anti-inflammatory, immunosuppressive, and antitumor activities (Liu, 2011 ; Li et al, 2016 ). It has also been shown to be very effective against many autoimmune and inflammatory diseases, especially RA (Fan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%